1967
DOI: 10.3733/hilg.v38n07p247
|View full text |Cite
|
Sign up to set email alerts
|

Iron requirement studies of navel orange trees in solution cultures

Abstract: Difficulties in controlling the supply of iron to citrus trees when grown in soil led the authors to use of nutrient solutions for this study. Twenty-four nucellar navel orange trees were grown for eleven years in individual tanks of nutrient solutions, out of doors. Eight of them were maintained at high-iron levels by regular additions of iron sulfate to the nutrient solutions. The remaining trees became iron deficient at various rates. Analyses of standard leaves, picked in the early fall season, provided a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
1992
1992

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In certain conditions, the iron content in chlorotic leaves decreased to around 60 ppm, yet this retains within the optimum range (Chapman et al, 1940;Smith et al, 1950;Wallihan et al, 1967;and Errfoleton et al, 1978) and still superior to the value reported by many authors for chlorotic citrus plants. Thus Chapman (1939) reported an iron content of 20 ppm in chlorotic lemon (Eureka), and Wallihan (1955) found an iron content of 16-33 and 24-68 ppm in cases of extreme and moderate chlorosis, respectively, and a 42-137 ppm in healthy leaves of orange, laron and grapefruit.…”
Section: Resultsmentioning
confidence: 52%
“…In certain conditions, the iron content in chlorotic leaves decreased to around 60 ppm, yet this retains within the optimum range (Chapman et al, 1940;Smith et al, 1950;Wallihan et al, 1967;and Errfoleton et al, 1978) and still superior to the value reported by many authors for chlorotic citrus plants. Thus Chapman (1939) reported an iron content of 20 ppm in chlorotic lemon (Eureka), and Wallihan (1955) found an iron content of 16-33 and 24-68 ppm in cases of extreme and moderate chlorosis, respectively, and a 42-137 ppm in healthy leaves of orange, laron and grapefruit.…”
Section: Resultsmentioning
confidence: 52%